PENGARUH PERMAINAN TARGET TERHADAP KETEPATAN SHOOTING UNDER RING EKSTRAKULIKULER BOLA BASKET DI SMPN 9 PURWAKARTA - Ayu Ika Khaira Salva; Aria Kusuma Yuda Ryanto; Astri Ayu Irawan; Dhika Bayu Mahardhika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of the research is the low ability of students to accurately performthe under ring shooting technique. The study employed a quantitative approachwith a quasi-experimental method using a One Group Pretest-Posttest Design.The sample consisted of 20 students selected through total random sampling of 20students. The instrument used was a shooting accuracy test administered beforeand after the intervention, which consisted of target-based training sessions. Dataanalysis was conducted using the Wilcoxon test. The results showed a significantdifference between the pretest and posttest scores with a significance value of0.000 (p < 0.05). This indicates that target games have a positive and significanteffect on improving students’ under ring shooting accuracy. Therefore, target-based training can be considered an effective alternative learning strategy toenhance basic basketball skills, especially under ring shooting.